INTERNATIONALIZATION OF MANUFACTURING AND GLOBAL VALUE CHAINS: ANALYSIS OF MANUFACTURING PROFILES BETWEEN EMBRAER AND BOEING - Souza, Crisomar Lobo de; Kaltenecker , Evodio; Santos, Alexandre Borges (Pensamento & Realidade, 2022)
This article aims to present the differences between the profile of plants and the global value chains (GVC) of two aircraft manufacturers, Embraer and Boeing. After, literature review about the theories of internationalization, global value chains, and internationalization of manufacturing. It is concluded that Embraer leads a value chain called Relational. At the same time, Boeing opted for the type called Hierarchy after a failed experience with the Relational type of value chain during the development of the 787 Dreamliner model.